Machine learning optimization of an electronic health record audit for heart failure in primary care. (23rd November 2021) - Raat, Willem; Smeets, Miek; Henrard, Severine; Aertgeerts, Bert; Penders, Joris; Droogne, Walter; Mullens, Wilfried; Janssens, Stefan; Vaes, Bert
Abstract: Aims: The diagnosis of heart failure (HF) is an important problem in primary care. We previously demonstrated a 74% increase in registered HF diagnoses in primary care electronic health records (EHRs) following an extended audit procedure. What remains unclear is the accuracy of registered HF pre‐audit and which EHR variables are most important in the extended audit strategy. This study aims to describe the diagnostic HF classification sequence at different stages, assess general practitioner (GP) HF misclassification, and test the predictive performance of an optimized audit. Methods and results: This is a secondary analysis of the OSCAR‐HF study, a prospective observational trial including 51 participating GPs. OSCAR used an extended audit based on typical HF risk factors, signs, symptoms, and medications in GPs' EHR. This resulted in a list of possible HF patients, which participating GPs had to classify as HF or non‐HF. We compared registered HF diagnoses before and after GPs' assessment. For our analysis of audit performance, we used GPs' assessment of HF as primary outcome and audit queries as dichotomous predictor variables for a gradient boosted machine (GBM) decision tree algorithm and logistic regression model. Of the 18 011 patients eligible for the audit intervention, 4678 (26.0%) were identified as possible HF patients and submitted for GPs' assessment in the audit stage. There were 310 patients with registered HF before GP assessment, of whom 146 (47.1%) were judged not to have HF by their GP (over‐registration). There were 538 patients with registered HF after GP assessment, of whom 374 (69.5%) did not have registered HF before GP assessment (under‐registration). The GBM and logistic regression model had a comparable predictive performance (area under the curve of 0.70 [95% confidence interval 0.65–0.77] and 0.69 [95% confidence interval 0.64–0.75], respectively). This was not significantly impacted by reducing the set of predictor variables to the 10 most important variables identified in the GBM model (free‐text and coded cardiomyopathy, ischaemic heart disease and atrial fibrillation, digoxin, mineralocorticoid receptor antagonists, and combinations of renin‐angiotensin system inhibitors and beta‐blockers with diuretics). This optimized query set was enough to identify 86% ( n  = 461/538) of GPs' self‐assessed HF population with a 33% reduction ( n  = 1537/4678) in screening caseload. Conclusions: Diagnostic coding of HF in primary care health records is inaccurate with a high degree of under‐registration and over‐registration. An optimized query set enabled identification of more than 80% of GPs' self‐assessed HF population.